Perceived utility of electrodiagnostic testing in critical illness myopathy and polyneuropathy: A survey of intensive care unit providers. Issue 1 (6th May 2022) - Isfort, Michael; McVerry, Bryan J.; Shutter, Lori; Kim, Minji; Lacomis, David
Abstract: Introduction/Aims: Critical illness myopathy (CIM) and critical illness polyneuropathy (CIP) are common disorders associated with substantial morbidity. Electrodiagnostic studies (EDx) are effective in diagnosing CIM/CIP and identifying mimicking conditions. We surveyed intensive care unit (ICU) providers to better understand their approach to ICU‐acquired weakness (ICU‐AW) and the perceived utility of EDx. Methods: This was a single health system, Web‐based survey of ICU providers. Results: Survey responses were received from 52 providers with a response rate of 22.1%. Most providers were somewhat familiar with CIM/CIP and median perceived prevalence was 30–49%. The majority (92.3%) of providers had no standard evaluation approach for ICU‐AW. Electrodiagnostic testing was commonly considered, but many providers obtained it infrequently in presumed CIM/CIP cases. Electrodiagnostic studies were used to rule out other causes of weakness or to confirm the diagnosis of CIM/CIP. Many providers ordered EDx within 1 wk of identifying weakness. Finally, EDx were overshadowed by personal experience as the most helpful management tool for ICU‐AW. Discussion: Overall, ICU providers perceive that CIM/CIP are commonly encountered, but they may not have a standard approach to evaluation. Clinical experience increased familiarity of ICU‐AW and is central to management. EDx results are usually thought to be helpful, albeit not often ordered, and more study is needed to determine when implementation is of most assistance. Increasing education and developing institutional standards may lead to increased awareness and improved evaluation of CIM/CIP, but more study is needed to determine if algorithmic approaches would change patient outcomes.